Pengaruh Tekanan Injeksi pada Suhu Mould yang Tidak Sesuai terhadap Low Length Material Plastik ABS dengan Tebal Produk 1MM - Widjaja, Hartono; Rahajo, Andika (Pusat Penelitian dan Pengabdian kepada Masyarakat (P3M) Politeknik Manufaktur Bandung (Polman Bandung), 2023)
One example of a plastic material is ABS (Acrylonitrile Butadiene Styrene) which is a type of thermoplastic plastic. Thermoplastics are organic synthetic materials that melt when heated and can be formed under the influence of pressure. In the book “Molding Simulation: Theory and Practice, there is a table of reasonable design values for the L/t ratio. The table states that the flow length of ABS material with a product thickness of 1mm is 100mm-200mm. This study aims to determine the flow length of ABS material at the lowest and highest injection pressures with a mold temperature of 25 °C (the correct plastic material mold temperature is 50 - 80 °C), to find out the comparison between the trial results and the reference table, to determine the effect of injection pressure on flow. length ABS plastic material on the long and short runners. Based on the conditions and parameters used in this study, it was found that the greater the injection pressure, the longer the resulting flow length and the mold temperature affecting the resulting flow length. And in order to obtain a flow length or flowability in accordance with the table of reasonable design values for the L/t ratio, the correct width of the product/specimen mold is 7.941 mm for the long runner and 12.687 mm for the short runner.